2020
DOI: 10.21608/ijma.2020.22013.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sublingual Misoprostol Prior to Insertion of Intrauterine Device in Women with no Previous Vaginal Delivery.

Abstract: Background:The intrauterine device [IUD] is a safe and effective method of contraception, fear of pain during insertion discourages some providers to recommend IUDs to women with no previous vaginal delivery. Aim of the work:The aim of the study is to evaluate sublingual misoprostol 200µg on the cervix one hour before IUD insertion; to facilitate IUD insertion in women with tight cervix or in whom did not deliver vaginally. Patients and Methods: The study was a double blinded randomized controlled trial, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, Elgharabawy et al ( 2020) and her research group found that the use of sublingual 200mcg misoprostol to facilitate IUD installation in women with a tight cervix had no effect on pain relief or IUD insertion ease; however, the results with misoprostol are better than placebo, but the difference is not statistically significant 21 . This could be attributed to different routes and timing as they used sublingual misoprostol 1 hour prior to insertion.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, Elgharabawy et al ( 2020) and her research group found that the use of sublingual 200mcg misoprostol to facilitate IUD installation in women with a tight cervix had no effect on pain relief or IUD insertion ease; however, the results with misoprostol are better than placebo, but the difference is not statistically significant 21 . This could be attributed to different routes and timing as they used sublingual misoprostol 1 hour prior to insertion.…”
Section: Discussionmentioning
confidence: 97%